Evaluation of the agdisp ground boom spray drift model - Woodward, S.J.R.; Connell, R.J.; Zabkiewicz, J.A.; Steele, K.D.; Praat, J.P. (New Zealand Plant Protection, 2008)
AGDISP is a wellestablished spray drift model that has been validated for aerial spraying of forests Recently a prototypical ground boom option has been added to AGDISP This was evaluated in the current study by collecting data from spray trials over a grass sward using a ground boom sprayer and representative application parameters Spray solutions were made up of water sticker adjuvant and a metal cation which was changed for each spray application Deposition from spray drift was measured by analyses of the cation deposits on artificial targets (plastic tapes) placed on the grass surface Measured deposition was compared with profiles calculated using AGDISP AGDISP overpredicted deposition from spray drift by a factor of 35100 outside the spray block Possible reasons for these discrepancies are given Options are to improve measured deposition and the algorithms for the deposition on the downwind swath of the spray block and evaporation of droplets